Medical pharmacology & theraupeutics - Waller, Derek; Sampson, Anthony P. (Elsevier, 2018)
This textbook on medical pharmacology and therapeutics provides a basis for learning about a safe and effective prescribing of modern medicines by including descriptions of the pathogenic mechanisms of the disease and where and how drugs have their actions and unwanted effects.